Validity of anthropometric equations for the estimation of body fat in older adults individuals from southern Brazil - Cassiano Ricardo Rech; Luiz Rodrigo Augustemak de Lima; Braian Alves Cordeiro; Edio Luiz Petroski; Francisco de Assis Guedes de Vasconcelos (Universidade Federal de Santa Catarina, 2010)
The objective of this study was to analyze the cross-validity of anthropometric equations for the estimation of body fat (%F) in Brazilian elderly individuals. A total of 180 elderly individuals (120 women and 60 men) ranging in age from 60 to 81 years were studied. Height, body weight and body perimeters were measured. Seven equations based on anthropometric measures were tested using the cross-validation criteria suggested by Lohman. Bland-Altman plots were used to determine the agreement of the equations with the reference method, with %F estimated by dual-energy X-ray absorptiometry (DEXA) serving as a reference. The body mass index of the group studied ranged from 18.4 to 39.3 kg/m2. Mean %F was 23.1% in men and 37.3% in women (range: 6 to 51.4%). The results showed no difference (p>0.05) between the equations of Tran and Weltmann and Deurenberg et al. and the DEXA measurement for men, with agreement of 68.2% (r=0.78) and 72.8% (r=0.74), respectively. For women, the equations of Tran and Weltmann and Gonçalves did not differ from the DEXA measurement (p> 0.05), with agreement of 66.0% (r=0.76) and 72.9% (r=0.75), respectively. In conclusion, the anthropometric equations proposed in the literature differ in terms of their predictive capacity of %F. Caution in using the %F predictive anthropometric equation in elderly is advised.